2005
DOI: 10.1063/1.1922590
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen content in doped and undoped BaPrO3 and BaCeO3 by cold neutron prompt-gamma activation analysis

Abstract: Proton uptake in undoped and Y-doped BaPrO 3 has been measured by cold neutron prompt-gamma activation analysis, and compared to the proton uptake in Gd-doped BaCeO 3 , as determined by the same technique. The conventional proton incorporation model of perovskites in which oxygen ion vacancies, generated by the introduction of the trivalent dopant onto the tetravalent perovskite site, are filled with hydroxyl groups upon exposure of the sample to H 2 O containing atmospheres, predicts that the proton concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…It has been reported that tetravalent Pr tends to become partially trivalent with a decrease in the partial pressure of oxygen. 27 The concentration of oxide ion vacancies increases for charge compensation, which benets the proton conduction.…”
Section: Conductivity Of Doped Bazromentioning
confidence: 99%
“…It has been reported that tetravalent Pr tends to become partially trivalent with a decrease in the partial pressure of oxygen. 27 The concentration of oxide ion vacancies increases for charge compensation, which benets the proton conduction.…”
Section: Conductivity Of Doped Bazromentioning
confidence: 99%
“…The traditional mechanism for proton incorporation in perovskites is directly tied to the dopant concentration. 15,27) When an ABO 3 perovskite is doped at the tetravalent B sites with trivalent ions, an oxygen vacancy results for every two doped sites. This vacancy dissolves water from the atmosphere into a hydroxyl, which fills the vacancy and a proton which quickly binds to an oxygen in the perovskite lattice.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite-type oxide BaPrO3 has an orthorhombic structure (Pbnm) with the lattice constant of a=6.201 Å, b=6.173 Å and c=8.712 Å at room temperature [1][2][3][4][5]. The BaPrO3 is a paramagnetic material with electron conduction in semiconducting region [5].…”
Section: Introductionmentioning
confidence: 99%
“…This material occurs the magnetic transition from paramagnetic phase to antiferromagnetic phase [6][7][8][9][10]. The structural and magnetic properties have been investigated in the research area of solid state physics [1][2][3][4][5][6][7][8][9][10]. In the research area of electrochemical, it is known that BaPrO3 exhibits high electron-proton mixed conduction in intermediate temperature region (600~300°C) when Yb 3+ ions are substituted into Pr 4+ site [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%